2022
DOI: 10.1111/epi.17331
|View full text |Cite
|
Sign up to set email alerts
|

Anterior nucleus of the thalamus deep brain stimulation vs temporal lobe responsive neurostimulation for temporal lobe epilepsy

Abstract: Objective: Based on the promising results of randomized controlled trials, deep brain stimulation (DBS) and responsive neurostimulation (RNS) are used increasingly in the treatment of patients with drug-resistant epilepsy. Drug-resistant temporal lobe epilepsy (TLE) is an indication for either DBS of the anterior nucleus of the thalamus (ANT) or temporal lobe (TL) RNS, but there are no stud-How to cite this article: Yang JC, Bullinger KL, Dickey AS, Karakis I, Alwaki A, Cabaniss BT, Anterior nucleus of the tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Strong objective evidence is often lacking to guide emerging neurostimulation applications. Retrospective comparisons have not found differences between VNS and RNS [8 ▪ ,9], DBS-ANT and RNS [10 ▪ ], and between RNS, DBS, VNS and cortical stimulation (with the possible increased efficacy of CSS in one single-centre comparison of this emerging neurostimulation method) [11 ▪ ]. Here, we focus on recent results and innovative aspects of neurostimulation, including targeted brain regions, uses of implanted hardware, stimulation programming and noninvasive approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Strong objective evidence is often lacking to guide emerging neurostimulation applications. Retrospective comparisons have not found differences between VNS and RNS [8 ▪ ,9], DBS-ANT and RNS [10 ▪ ], and between RNS, DBS, VNS and cortical stimulation (with the possible increased efficacy of CSS in one single-centre comparison of this emerging neurostimulation method) [11 ▪ ]. Here, we focus on recent results and innovative aspects of neurostimulation, including targeted brain regions, uses of implanted hardware, stimulation programming and noninvasive approaches.…”
Section: Introductionmentioning
confidence: 99%
“…These findings re-iterate the potential use of RNS to prognosticate results of ANT DBS therapy and/or provide a biomarker to guide ANT DBS programming, although the usefulness of such in a patient receiving hippocampal RNS is dubious. Indeed, although we conceived that ANT DBS may work in this patient who failed bilateral hippocampal RNS because of a possible more widespread engagement of limbic circuitry, the failure to respond to both hippocampal RNS and ANT DBS does, indirectly, support a similarity in their mechanism(s) of action, also supported by our recent finding of similar magnitudes of clinical benefits in cohorts of temporal lobe epilepsy patients undergoing one or the other of these therapies [9].…”
Section: Discussionmentioning
confidence: 80%
“…Clinical trials have demonstrated long-term median seizure reduction of 70% in patients with mesial temporal lobe epilepsy (MTLE) using the RNS system [7]. DBS of the anterior nucleus of the thalamus (ANT) has shown comparable long-term outcomes to RNS [8], including in a recent single-center series [9], although there are no head-to-head trials directly comparing the efficacy of RNS to DBS.…”
Section: Introductionmentioning
confidence: 99%
“…For generalized epilepsies using DBS, anterior thalamic nucleus and centromedian thalamic nucleus lead locations had a 60.8% and 73.4% mean seizure reduction (Vetkas et al ., 2022). In a comparison of patients with temporal lobe epilepsy with DBS and the RNS System, median seizure reduction was 58% after 12-15 months for 26 ANT-DBS patients and 70% for 32 patients with TL-RNS (Yang et al ., 2022). DBS for epilepsy does not produce a continuous train of pulses as typical for movement disorders, but rather follows a 1-minute ON cycle and 5-minute OFF cycle.…”
Section: Discussionmentioning
confidence: 99%